Pattern and Frequency of Anti-nuclear Antibody Positivity in Paediatric Rheumatic Diseases (Bangladesh Journal of Child Health, 2019)
Background: Anti-nuclear antibodies (ANAs) are specific antibodies directed against a variety of nuclear antigens detected in the serum of patients with many rheumatic and non-rheumatic diseases.These antibodies are not only involved in the pathogenesis, but also constitute the basis for diagnosis and treatment of paediatric rheumatic diseases. The objective of the study was to identify the patterns and frequency of ANA positivity in Paediatric Rheumatic Diseases.Methodology: It was a retrospective study. Fourteen hundred and sixty eight records of paediaric rheumatology patients were analyzed. Statistical analysis were done to observe the frequency and association of different patterns of ANA in Juvenile idiopathic arthritis and systemic lupus erythematosus patients.Results: Among the 1468 patients of PRDs, frequency of JIA cases was the highest (65 %) followed by SLE, Scleroderma, juvenile dermatomyositis, and others. Among the 261 PRD patients ANA positivity was 65%. ANA positivity was 100%, 92%, 40% and 31.5% in Mixed connective tissue disease, SLE, JDM and Scleroderma patients respectively. Homogenous staining pattern was found in 59% and speckled pattern in 22.9%. There was significant association between ANA positivity and uveitis in oligoarticular JIA patients. Significant association was also found between homogeneous patterns of ANA and renal involvement in SLE patients.Conclusion: ANA positivity was highest in MCTD cases followed by SLE cases. Majority of SLE cases had homogeneous pattern of ANA.Staining patterns of ANA had significant association with the clinical manifestations in SLE and JIA cases.Bangladesh J Child Health 2019; VOL 43 (1) :21-26